Optimizational Therapy's Efficacy for People Suffering from Anxiety Symptoms (Journal of Advances and Scholarly Researches in Allied Education, 2023)
The primary goal of this empirical study is to determine whether or not occupational therapy canimprove the well-being of elderly people living in an institutional setting who are experiencing symptomsof depression, social isolation, and anxiety. The widespread occurrence of stress illnesses has severelylimited many people's capacity to take part in everyday activities. Forty persons now residing at the Homefor persons with Physical Disabilities serve as the experimental background for the current study. Multiplesclerosis, spina bifida, muscular dystrophy, limb abnormalities, cerebral palsy, paraplegia, heart attack,stroke, etc. are only few of the conditions that the people who get this social assistance have. Theircognitive abilities are all still intact. To aid in clinical diagnoses and psychopathology screening, aquestionnaire was developed based on the PAI (Personality Assessment Inventory) and administered toa sample population of adults in a controlled trial. Items from the PAI were chosen because of theirability to identify anxiety symptoms and phenomenology and because they were employed in the currentinvestigation. The Anxiety Scale is a self-report assessment of personality characteristics that arecorrelated with anxiety. The scale includes sections measuring worry in three different ways mentally,emotionally, and physically. Occupational therapy has traditionally placed a strong focus on employmentand the human element in the workplace, and its methodology is organised around iterative cycles ofproblem identification and solution development. The post-treatment outcomes are very suggestive ofoccupational therapy's efficacy. The number of people with anxiety dropped from 37 (93.2) beforeoccupational therapy was carried out to 18 (47.7), a reduction of nearly 50 this is only one of theimproved indicators. The current research suggests that occupational therapy is the most often usedkind of rehabilitation treatment in public facilities. It's a chance to let go of stress, worry, wrath,discontent, disappointment, insult, and hatred.